(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Lymphedema is a chronic disorder of the lymphatic system characterized by interstitial fluid accumulation resulting from impaired or obstructed lymphatic drainage. Its clinical manifestations are often nonspecific, making early diagnosis challenging. Lymphoscintigraphy is a nuclear medicine technique that enables direct functional assessment of the lymphatic system and is currently regarded as the gold standard for the diagnosis of lymphedema. Case summary: We report the case of a 57-year-old female patient who was admitted with long-standing swelling of the left lower limb. She had no history of surgery or trauma. Doppler ultrasound of the lower extremity veins showed no evidence of venous thrombosis or valvular insufficiency. Clinical examination revealed firm edema of the left lower limb, classified as grade IV according to the Cheng classification, raising suspicion of lymphedema. Intervention and outcome: Lower-limb lymphoscintigraphy using Technetium-99m Human Serum Albumin (99mTc-HSA) demonstrated complete lymphatic obstruction of the left lower limb (T4 according to the Cheng classification), characterized by radiotracer retention at the injection site, dermal backflow, and absence of visualization of inguinal–iliac lymph nodes. The patient subsequently underwent lymphatic reconstruction using autologous vein grafting. After one month of follow-up, a marked improvement in limb edema was observed. Conclusion: This case illustrates the role of lymphoscintigraphy in supporting the diagnosis and staging of lymphedema, while also guiding treatment selection and evaluating the effectiveness of surgical interventions.